Gulliver's travels [compact disc, unabridged] - Swift, Jonathan, 1667-1745 (Tantor Audio, 2008)
The voyages of an Englishman carry him to such strange places as Lilliput, where people are six inches tall; Brobdingnag, a land of giants; an island of sorcerers; and a country ruled by horses.